2018
DOI: 10.1007/s13197-018-3050-0
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds and “in vitro” antioxidant activity of some traditional and non-traditional cold-pressed edible oils from Macedonia

Abstract: The bioactive compounds and "in vitro" antioxidant activity measured by three antioxidant assays of some traditional and non-traditional cold-pressed edible oils from Macedonia were object of this study. The fatty acid composition showed dominance of monounsaturated oleic acid in "sweet" and "bitter" apricot kernel oils with percentages of 66.7 ± 0.5 and 57.8 ± 0.3%, respectively. The most dominant fatty acid in paprika seed oil was polyunsaturated linoleic acid with abundance of 69.6 ± 2.3%. The most abundant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…They are an important nutritional compound that can reduce serum LDL cholesterol, as well as atherosclerotic risk. The highest level of total phytosterols was observed in pepper seed oil (over 5500 mg/kg) in the study by Veličkovska et al [ 39 ]. The most dominant phytosterol in pepper seed oil was Δ5-avenasterol with the level of 1141 ± 8.1 mg/kg, which amounts to one-fifth of the total phytosterols content in pepper seed oil.…”
Section: Chemical Composition Of Pepper Seed Flour and Pepper Seed Oilmentioning
confidence: 99%
See 3 more Smart Citations
“…They are an important nutritional compound that can reduce serum LDL cholesterol, as well as atherosclerotic risk. The highest level of total phytosterols was observed in pepper seed oil (over 5500 mg/kg) in the study by Veličkovska et al [ 39 ]. The most dominant phytosterol in pepper seed oil was Δ5-avenasterol with the level of 1141 ± 8.1 mg/kg, which amounts to one-fifth of the total phytosterols content in pepper seed oil.…”
Section: Chemical Composition Of Pepper Seed Flour and Pepper Seed Oilmentioning
confidence: 99%
“…Saturated fatty acids are palmitic and stearic acids, and oleic and linoleic acids are the main unsaturated fatty acids. According to Table 2 , linoleic acid content ranged from 67.8% [ 16 ] to 77.9% [ 4 ], oleic acid content was between 4.6% [ 39 ] and 14.6% [ 16 ], palmitic acid content was between 10.6% [ 4 ] and 14.4% [ 16 ] and stearic acid content was between 2.4% (Chouaibi) and 4.1% Matthaus). Konscek et al [ 32 ] showed that different varieties and growing seasons did not change the fatty acid composition of pepper seed oil.…”
Section: Chemical Composition Of Pepper Seed Flour and Pepper Seed Oilmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenolic content of the nuts may decrease or even prevent the processes of oxidative stress-related disorders (Isfahlan et al, 2010;Alkhatib, 2020;Subhashinee et al, 2006). Also, Almond oil can be helpful for the improvement of the immune system and the prevention of many degenerative diseases (Kostadinović Veličkovska et al, 2018). On the other hand, almond kernel has shown prebiotic properties (Gibson and Roberfroid, 1995) while probiotics are supposed to be useful in the management of COVID-19 infection (Figure 2) (Giannoni et al, 2020).…”
Section: Almond Morabbamentioning
confidence: 99%